Human activities and changes in the gut microbiome: A perspective - Fahrul Nurkolis; Nelly Mayulu; Nadia Yasmine; Dwi Sari Puspaningtyas; Nurpudji Astuti Taslim (Human Nutrition & Metabolism, 2022)
The microbiome plays a role in maintaining the balance of the environment. However, the microbiome in the ecosystem has been affected by climate and environmental changes. The human activity that interferes with the balance of nature affects the composition of the microbiome in both the environment and the human body. Climate change drastically influences different environmental cycles. The microbiome responds and adapts to changes in ecological conditions, which results in a change in the balance of the microbiome in nature. It will adversely affect the microbiome imbalance in the human body, which affects the health of human. Therefore, this article will consider a related cycle of effects and the effects of human activity on the environment and the microbiome. The article's perspective should provide a clearer view of the effects of human activity on the changes in the gut microbiome. By humans - because humans - for humans, that is a fitting description of the disease cycle affected by the changes in the gut microbiome. Human activity results in changes in the composition of the soil microbiome and thus the quality and nutrients of food change as well. Changes in the quality of nutrients in the food consumed will cause an imbalance in the intestinal microbiome.